Open Stabilization Procedures of the Shoulder in the Athlete: Indications, Techniques, and Outcomes - Haratian A; Yensen K; Bell JA; Hasan LK; Shelby T; Yoshida B; Bolia IK; Weber AE; Petrigliano FA (Dove Medical Press, 2021)
Aryan Haratian, Katie Yensen, Jennifer A Bell, Laith K Hasan, Tara Shelby, Brandon Yoshida, Ioanna K Bolia, Alexander E Weber, Frank A Petrigliano USC Epstein Family Center for Sports Medicine at Keck Medicine of USC, Los Angeles, CA, USACorrespondence: Frank A PetriglianoUSC Epstein Family Center for Sports Medicine at Keck Medicine of USC, 1520 San Pablo Street, Suite 2000, Los Angeles, CA, 90033, USATel +1 323 442-5822Email fpetrigliano@gmail.comAbstract: Shoulder instability is a relatively common injury especially in the young athletic population and its surgical management continues to remain a controversial topic in sports medicine orthopedics. Anterior instability is the most common type encountered and is estimated to have an incidence rate of 0.08 per 1000 person-years in the general population; however, this figure is likely higher in the young athletic population. While in recent practice, arthroscopic surgery has become the new gold standard for management, reported failure rates as high as 26% and high recurrence rates in specific subpopulations such as young men in high collision sports have led to the consideration of alternative open procedures such as open Bankart repair, Latarjet, capsular shift, and glenoid bone grafting. These procedures may be preferred in specific patient subgroups such as young athletes involved in contact sports and those with Hill-Sachs defects and multidirectional instability, with postoperative recurrence rates of instability as low as 10%. The purpose of this review is to provide an overview of different open surgical techniques in the management of shoulder instability and summarize patient outcomes including recurrence rates for shoulder instability, return to sport, range of motion (ROM), muscle strength, and complications either individually by procedure or in comparison with other techniques, with special focus on their impact in the athletic population.Keywords: open shoulder stabilization, athletes, anterior instability, open Bankart repair, open Latarjet, open capsular shift